2015
DOI: 10.12659/pjr.895872
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Absence of Left Circumflex Presenting After an Emotional Stressor

Abstract: SummaryBackgroundAbsence of the left circumflex artery (LCX) is an extremely rare congenital anomaly of the coronary circulation. While some coronary circulation anomalies are associated with significant complications, including sudden cardiac death and premature atherosclerosis, absence of the LCX is largely considered benign, though it has been associated with exertional chest pain, which may mimic acute coronary syndrome. Diagnosis is made when heart catheterization is performed in the work up for acute cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 6 publications
(11 reference statements)
0
11
0
3
Order By: Relevance
“…It has been hypothesized that symptoms on exertion are possibly secondary to a 'steal' phenomenon. This phenomenon arises in situations of increased metabolic demands in the LCx territory leading to the diversion of blood flow to these regions resulting in ischemic changes in the LAD or RCA territories which can mimic an acute coronary event [7]. This can manifest as perfusion defects on stress thallium study [6].…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that symptoms on exertion are possibly secondary to a 'steal' phenomenon. This phenomenon arises in situations of increased metabolic demands in the LCx territory leading to the diversion of blood flow to these regions resulting in ischemic changes in the LAD or RCA territories which can mimic an acute coronary event [7]. This can manifest as perfusion defects on stress thallium study [6].…”
Section: Discussionmentioning
confidence: 99%
“…Congenital absence of left circumflex artery is an incidental benign finding on coronary angiography and most of these patients present with chest pain on exertion. [7][8][9][10][11] Varela et al [7] reported a case of congenitally absent left circumflex with block of right coronary artery causing inferolateral and posterior wall myocardial infarction. The various investigations available to diagnose this rare entity include transthoracic, transoesophageal echocardiography, cardiac magnetic resonance imaging, MDCT coronary angiography and invasive coronary angiography.…”
Section: Discussion Of Managementmentioning
confidence: 99%
“…The etiology of chest pain in these patients is not clearly understood. One of the explanations offered in literature is a steal phenomenon during exertion, where there may be transient ischemia in territories fed by the RCA and LAD due to the diversion of blood flow to anatomical regions usually fed by the left circumflex artery [ 3 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to its uncommon nature, diagnosis can be challenging, especially among patients who present with acute cardiac symptoms. It may initially be misdiagnosed as complete occlusion of the left circumflex artery [ 3 ]. A better understanding of the natural history and clinical implications of this condition may allow us to diagnose and manage this condition with an algorithmic approach.…”
Section: Introductionmentioning
confidence: 99%